Randomized Trial Demonstrating No Translocation of Intact Intestinal Bacteria During Hemodialysis or Hemodiafiltration - Paul A. Rootjes; Muriel P.C. Grooteman; Andries E. Budding; Hetty J. Bontkes; Gertrude Wijngaarden; Menso J. Nubé; Camiel L.M. de Roij van Zuijdewijn (Kidney International Reports)
Introduction: The low incidence of intradialytic hypotension (IDH) in high-volume (HV) hemodiafiltration (HDF) may help in maintaining gut perfusion during treatment. Preservation of gut endothelial integrity would limit or prevent bacterial translocation and subsequent systemic inflammation, which may contribute to the low mortality rate in HV-HDF. Methods: Forty patients were cross-over randomized to standard (hemodialysis [HD]) (S-HD), cool HD (C-HD), and HDF (low-volume [LV] and HV, convection volume (CV) of 15 L and ≥ 23 L per session, respectively), each for 2 weeks. Quantitative assessment of microbial DNA (mDNA) in blood was performed before and after dialysis by 16S to 23S interspace profiling after DNA isolation. The intradialytic acute phase response (APR) was evaluated by high-sensitivity C-reactive protein (hs-CRP), interleukin-6 receptor (IL-6R), soluble CD14 (sCD14), and vascular-cell-adhesion molecule-1 (VCAM-1). Differences between modalities were primary objectives. Results: mDNA was absent from all samples. IL-6R, sCD14, and VCAM-1 increased equally in all modalities (median increase: 12.5%, 14.0%, 14.8%, respectively; P < 0.05). hs-CRP increased only in C-HD and HV-HDF (median increase: 12.6%, P < 0.05). After correction for hemoconcentration, most APR markers decreased (median: sCD14, −11.3% and VCAM-1, −14.4% in all modalities; IL-6R, −13.4% in C-HD, LV-HDF, and HV-HDF; P < 0.05). hs-CRP only decreased in C-HD (−13.5%, P = 0.004). Conclusion: From this study, we conclude as follows: (i) circulating mDNA could not be demonstrated; (ii) in the crude analysis, a similar APR was noted in all modalities, individual markers remained stable or declined after correction for hemoconcentration; and (iii) because neither bacterial translocation nor an APR was observed in either modality, it is highly unlikely that the superior survival of HV-HDF is explained by a superior preservation of gut integrity.